Association between serum potassium and Parkinson’s disease in the US (NHANES 2005–2020) - Zhou, Xue; Zhao, Jingtong; Liu, Yang; Sun, Xiaozhou; Li, Xuefeng; Ren, Jixiang; Li, Qingjie; Han, Dong; Pan, Ting; Shi, Yingqi; Wu, Dalong; Chen, Xinhua (Frontiers in Neuroscience, 2024)
Background：Evaluating the correlation between serum potassium and Parkinson's disease( PD) in US adults. Methods：A cross-sectional study was conducted on 20,495 adults aged 40 years or older using NHANES data from 2005 to 2020. The study utilized one-way logistic regression and multifactorial logistic regression to examine the correlation between serum potassium levels and PD. Additionally, a smoothed curve fitting approach was employed to assess the concentration-response relationship between serum potassium and PD. Stratified analyses were carried out to investigate potential interactions between serum potassium levels and PD with variables such as age, sex, race, marital status, education, BMI, smoking and medical conditions like coronary, stroke, diabetes, hypertension, and hypercholesterolemia. Results ： In this study, a total of 20,495 participants, comprising 403 PD and 20,092 non-PD individuals, were included. After adjusted for covariates, multivariable logistic regression revealed that high serum potassiun level was an independent risk factor for PD (OR:1.86, 95%CI:1.45~2.39, P <0.01).The linear association between serum potassium and PD was described using fitted smoothing curves. Age, sex, race, education, marital, BMI, coronary, stroke, diabetes, hypertension and hypercholesterolemia were not significantly correlated with this positive connection, according to subgroup analysis and interaction testing (P for interaction > 0.05). Conclusion： Serum potassium levels are elevated in patients with Parkinson's disease compared to non-PD patients. Additional prospective studies are required to explore the significance of serum potassium levels in individuals with Parkinson's disease.